A Mixed Comparisons of Different Intensities and Types of Physical Exercise in Patients With Diseases Related to Oxidative Stress: A Systematic Review and Network Meta-Analysis - Lu, Zhenghui; Xu, Yining; Song, Yang; Bíró, István; Gu, Yaodong (Frontiers in Physiology, 2021)
The balance of oxidative and antioxidant systems is of great importance to the human body. Physical exercise, as one of the ways to improve physical health, seems to modulate this balance. However, different intensities and types of physical exercise have other effects on the treatment of unhealthy people. To understand the impact of exercise training on the oxidative and antioxidant systems of adults with oxidative stress-related disorders, a network meta-analysis was used to compare the mixed effects of different intensities and types of exercise training. This systematic review included all eligible RCTs from PubMed, Medline, Cochrane Library, and CINAHL. Eleven of the studies met the inclusion criteria (at study completion, n = 666 participants). Seven studies reported that the level of MDA decreased significantly after exercise (p < 0.05), and 3 studies reported that the level of SOD increased significantly after exercise (p < 0.05). In conclusion, long-term high-intensity aerobic training and Tai Chi or Yoga can effectively improve oxidative stress in unhealthy people. In addition, different types of diseases on the effect of exercise intervention seems to be other, diabetes and chronic kidney patients using moderate-intensity aerobic training or Tai chi and Yoga effect are better; Moderate-intensity aerobic training had a better impact on OS improvement in patients with irritable bowel syndrome and severe depression. However, more research is needed to determine the effects of different levels and types of physical activity on oxidative stress in unhealthy populations. Systematic Review Registration: PROSPERO identifier: CRD42021242025. https://www.crd.york.ac.uk/prospero/.